Analytical Challenges and Metrological Approaches to Ensuring Dietary Supplement Quality: International Perspectives - Durazzo, Alessandra; Sorkin, Barbara C.; Lucarini, Massimo; Gusev, Pavel A.; Kuszak, Adam J.; Crawford, Cindy; Boyd, Courtney; Deuster, Patricia A.; Saldanha, Leila G.; Gurley, Bill J.; Pehrsson, Pamela R.; Harnly, James M.; et al. (Frontiers in Pharmacology, 2022)
The increased utilization of metrology resources and expanded application of its’ approaches in the development of internationally agreed upon measurements can lay the basis for regulatory harmonization, support reproducible research, and advance scientific understanding, especially of dietary supplements and herbal medicines. Yet, metrology is often underappreciated and underutilized in dealing with the many challenges presented by these chemically complex preparations. This article discusses the utility of applying rigorous analytical techniques and adopting metrological principles more widely in studying dietary supplement products and ingredients, particularly medical plants and other botanicals. An assessment of current and emerging dietary supplement characterization methods is provided, including targeted and non-targeted techniques, as well as data analysis and evaluation approaches, with a focus on chemometrics, toxicity, dosage form performance, and data management. Quality assessment, statistical methods, and optimized methods for data management are also discussed. Case studies provide examples of applying metrological principles in thorough analytical characterization of supplement composition to clarify their health effects. A new frontier for metrology in dietary supplement science is described, including opportunities to improve methods for analysis and data management, development of relevant standards and good practices, and communication of these developments to researchers and analysts, as well as to regulatory and policy decision makers in the public and private sectors. The promotion of closer interactions between analytical, clinical, and pharmaceutical scientists who are involved in research and product development with metrologists who develop standards and methodological guidelines is critical to advance research on dietary supplement characterization and health effects.